The Influence of Individual Characteristics, Training and Career Development on Employee Performance PT Hotel KTM Resort - Maisyarah; Saputra, Asron (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This study analyzes the influence of individual characteristics, Training, and career development on employee performance at PT Hotel KTM Resort in Batam, Indonesia. Despite the significant role of human resources in the hospitality industry, challenges such as low employee focus and delayed career progression hinder performance. Using quantitative methods, the research examined data from 115 employees to evaluate the effects of these variables. The findings indicate that training and career development significantly impact employee performance, while individual characteristics do not considerably influence performance outcomes. Training programs tailored to employee needs and structured career development pathways enhanced job satisfaction, motivation, and overall productivity. Furthermore, simultaneous analysis revealed that these variables collectively explain 37.7% of performance variation, suggesting other influencing factors. Recommendations include improving training quality, creating clear career advancement opportunities, and adopting holistic HR management practices focusing on supportive leadership and work environments. By implementing these strategies, PT Hotel KTM Resort can enhance employee engagement, reduce turnover rates, and improve service quality. These insights contribute to the hospitality sector's broader understanding of human resource management, emphasizing the importance of investment in employee development initiatives. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 4: Quality EducationSDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and Infrastructure